The Gower Prelude to the Marcher Rising of 1321: A Question of Evidence. (1st July 2014) - Furby, Bridget Wells-
It has long been considered that the seizure of Gower by Edward II in 1320 was at least in part the result of an attempted swindle by its lord William de Briouze who tried to sell the lordship to a number of different buyers. A reassessment of the chronicle and other contemporary evidence shows that it is more likely that Briouze made an arrangement with his son- in- law John de Mowbray, and with the earl of Hereford, which was not unusual and that the younger Despenser's interest in Gower was less wholesome than that of a potential buyer.